(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Abstract: This article thoroughly examines the theoretical foundations of corpus linguistics and its stages of development. It also provides a detailed discussion of its methodology, key concepts, technology used, and important scientists who helped this field grow.